Caudal block with analgosedation – a superior anaesthesia technique for lower abdominal surgery in paediatric population - Adisa Šabanović Adilović; Nermina Rizvanović; Harun Adilović; Malik Ejubović; Azur Jakić; Hajrija Maksić; Dušica Simić (Medicinski glasnik, 2019)
Aim: To compare intraoperative hemodynamic and respiratory stability and postoperative emergence delirium between two anaesthesia regimens in children (caudal block with intravenous continuous analgosedation versus general endotracheal anaesthesia) and intensity of postoperative pain and quality of postoperative analgesia. Method: Forty children aged 2-6 years who underwent lower abdominal surgery were randomized depending on performed anaesthesia into two groups: caudal block with analgosedation (group CB) and general endotracheal anaesthesia (group GA). Intraoperative hemodynamic and respiratory stability were evaluated measuring systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial blood pressure (MAP), heart rate (HR) and arterial oxygen saturation (SaO 2) in preinduction (t 0), at the moment of surgical incision (t 1), 10 minutes after surgical incision (t 2) and at the time of skin suturing (t 3). Postoperative emergence delirium was evaluated using Paediatric Anaesthesia Emergence Delirium score (PAED). Postoperative pain was evaluated by Children's and Infants' Postoperative Pain score (CHIPPS). Both scores were recorded every 5 minutes during first half hour postoperatively, additionally after 60 minutes postoperatively for CHIPPS score. Results: SBP, DBP and MAP were lower at t 1 (p<0.0001), t 2 (p<0.05) and t 3 (p<0.001) in the group CB. HR was lower at all studied time points (p<0.005) in the group CB. SaO 2 was lower in the CB group but comparable with the GA group. PAED and CHIPPS scores were lower at 5, 10, 15, 20 and 25 minutes postoperatively (p<0.001) in the CB group. Conclusion: Caudal block with analgosedation provides better control of intraoperative hemodynamic conditions, postoperative emergence delirium and postoperative pain than general endotracheal anaesthesia.
Keywords: analgesia; children; hemodynamic; emergence delirium; postoperative pain